A mechanism regulating the onset of Sox2 expression in the embryonic neural plate. - Costis Papanayotou; Anne Mey; Anne-Marie Birot; Yasushi Saka; Sharon Boast; Jim C Smith; Jacques Samarut; Claudio D Stern (PLoS Biology)
In vertebrate embryos, the earliest definitive marker for the neural plate, which will give rise to the entire central nervous system, is the transcription factor Sox2. Although some of the extracellular signals that regulate neural plate fate have been identified, we know very little about the mechanisms controlling Sox2 expression and thus neural plate identity. Here, we use electroporation for gain- and loss-of-function in the chick embryo, in combination with bimolecular fluorescence complementation, two-hybrid screens, chromatin immunoprecipitation, and reporter assays to study protein interactions that regulate expression of N2, the earliest enhancer of Sox2 to be activated and which directs expression to the largest part of the neural plate. We show that interactions between three coiled-coil domain proteins (ERNI, Geminin, and BERT), the heterochromatin proteins HP1alpha and HP1gamma acting as repressors, and the chromatin-remodeling enzyme Brm acting as activator control the N2 enhancer. We propose that this mechanism regulates the timing of Sox2 expression as part of the process of establishing neural plate identity.